KINERJA KOMISI PENEGAK ETIKA PEMERINTAHAN DAERAH (KPEPD) DALAM MENGIMPLEMENTASIKAN PERDA NO.1 TAHUN 2008 TENTANG ETIKA PEMERINTAHAN DAERAH DI KOTA SOLOK PROVINSI SUMATERA BARAT - Perrara, Satra; Tua R.F.S, Harapan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Ethics Enforcement Commission Regional Government (KPEPD) is an independent agency established by the government of Solok as an institution functioning supervise and follow up ethics violations committed by government officials and the community Solok. Ethics of local government is a set of moral values and ethics as a guide in the act, behave, act, and say to the organizers of the local government and the community. Ethics of local government is designed as a basic rule that the state officials and the public aware and not in violation of the law. In fact in the ethics enforcement efforts in Solok KPEPD rated by many parties have not done performance in line with expectations, as an example, there are many ethical violations that occur are not processed properly by KPEPD.The purpose of this study was to analyze the performance of KPEPD and the factors that influence it. This study uses qualitative descriptive methods, data collection techniques by observation and interviews in which the parties involved in KPEPD and officials who drafted the regulations ethics as an informant. This research using the Theory of Performance Assessment Criteria Gomes.The results of this research shows that the performance of KPEPD overall compliance with the applicable procedures, but in the process of monitoring and enforcement of sanctions KPEPD find many obstacles, one of which is not directly inflict punishment on officials who abuse because all authority sanctioning returned to duty or the institution where the work ethic unscrupulous offenders. Other constraints affecting KPEPD is the socialization of regulation and its facilities and infrastructure are considered inadequate to date.Keywords: Performance and Ethical Governance